The unruly ocean - Techera, Erika J., author. Link
1 online resource.
Keywords: "This book introduces non-specialist readers to the history of how human societies have sought to control, use and exploit our oceans, seas and shorelines over time in different geographical and cultural contexts. Oceans, Seas and Shorelines in Law examines the development of the modern international legal regime - the law of the sea, maritime law, marine environmental and pollution law, fisheries regulation, and underwater cultural heritage law - and considers how effective these laws have been in addressing the many challenges facing marine and coastal environments ranging from piracy and war to oil spills and the extraction of marine resources. It concludes by discussing the socio-ecological crises facing the world's oceans, seas and shorelines, and explores current ideas for reimagining a legal regime that restores the health of our oceanic realm and offers a more holistic, transboundary, rights-based approach to ocean governance. This book will be of value to law and non-law undergraduate and postgraduate students, as well as research scholars and other educated audiences interested in a legal history of the world's oceans, seas and shorelines"--